P15.11.A 18F-Fluciclovine PET/CT to distinguish radiation necrosis from tumour progression in brain metastases treated with stereotactic radiosurgery: results of a prospective pilot study. (5th September 2022) - Tom, M C; DiFilippo, F; Smile, T; Jones, S E; Suh, J H; Murphy, E S; Yu, J S; Mohammadi, A M; Barnett, G H; Angelov, L; Huang, S S; Wu, G; et al.
Abstract: Background: Amino acid PET radiopharmaceutical, 18 F-fluciclovine, shows increased uptake in brain tumors relative to normal tissue and may be a useful tool for detecting recurrent brain metastases. Here, we report results from a prospective pilot study evaluating the use of 18 F-fluciclovine PET/CT to distinguish radiation necrosis from tumour progression among patients with brain metastases treated with stereotactic radiosurgery (SRS). Material and Methods: The primary objective was to estimate the accuracy of 18 F-fluciclovine PET/CT in distinguishing radiation necrosis from tumour progression. The trial included adults with brain metastases who underwent SRS and presented with a follow up MRI brain (with DSC MR perfusion) which was equivocal for radiation necrosis versus tumour progression. Within 30 days of equivocal MRI brain, patients underwent an 18 F-fluciclovine PET/CT (Siemens mCT) acquired 5-15 min post-injection with images generated by PSF reconstruction. Quantitative metrics for each lesion were documented and lesion to normal brain SUVmean ratios were calculated. The reference standard for diagnosis of radiation necrosis vs tumour progression was clinical follow up with MRI brain every 2-4 months until multidisciplinary consensus or tissue confirmation. Results: Of 16 patients enrolled between 7/2019-11/2020, 1 patient died prior to diagnosis, allowing 15 evaluable subjects with 20 lesions. Primary histology was NSCLC in 9 (45%) lesions, breast in 7 (35%), melanoma in 3 (15%), and endometrial in 1 (5%). The final diagnosis was radiation necrosis in 16 (80%) lesions and tumour progression in 4 (20%). SUVmax was a statistically significant predictor of tumour progression (P = 0.011), with higher SUVmax values indicative of tumour progression. The area under the ROC curve was 0.833 (95% CI: 0.590, 1.0). A cutoff of 4.3 provided a sensitivity to identify tumour progression of 1.0 (4/4) and specificity to rule out tumour progression of 0.63 (10/16). SUVmean (P = 0.018), SUVpeak (P = 0.007), and SUVpeak/normal (P = 0.002) also reached statistical significance as predictors of tumour progression, with higher SUVmax values indicative of tumour progression. SUVmax/normal (P = 0.1) and SUVmean/normal (P = 0.5) were not statistically significant. The AUC for SUVmax was not significantly higher than the AUCs for the other quantitative variables (P-values > 0.2). Conclusion: In this prospective pilot study, 18 F Fluciclovine PET/CT demonstrated promising accuracy to distinguish radiation necrosis from tumour progression among patients with brain metastases previously treated with SRS. Using SUVmax, a cutpoint of 4.3 provided a sensitivity of 1.0 and specificity of 0.63. Confirmatory phase II and III studies are ongoing.